Role of the transverse field in inverse freezing in the fermionic Ising spin-glass model - Magalhaes S.G. (2008)
We investigate the inverse freezing in the fermionic Ising spin-glass model in a transverse field Γ. The grand canonical potential is calculated in the static approximation, replica symmetry, and one-step replica symmetry breaking parisi scheme. It is argued that the average occupation per site n is strongly affected by Γ. As a consequence, the boundary phase is modified and, therefore, the reentrance associated with the inverse freezing is modified too. © 2008 The American Physical Society.